2016
DOI: 10.1016/j.ejfs.2015.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Sexual dimorphism of maxillary sinus using cone beam computed tomography

Abstract: The aim of this study was to evaluate the sexual dimorphism of maxillary sinus dimensions using the CBCT imaging modality. Thirty CBCT scans of bilateral maxillary sinuses (60 maxillary sinuses) were retrospectively selected and the height, width, and depth of the sinuses were measured. All data were subjected to descriptive and discriminative functional analysis with generation of multiple logistic regression model and ROC analysis.The overall values of the parameters were significantly greater in the males a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
18
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(38 citation statements)
references
References 18 publications
(23 reference statements)
5
18
1
1
Order By: Relevance
“…Thus height of the MS was the differentiation parameter which could be used to sex determination with an overall accuracy. The results achieved in this study were in agreement with several pervious studies (7)(8)(9) .…”
Section: Discussionsupporting
confidence: 93%
“…Thus height of the MS was the differentiation parameter which could be used to sex determination with an overall accuracy. The results achieved in this study were in agreement with several pervious studies (7)(8)(9) .…”
Section: Discussionsupporting
confidence: 93%
“…In addition, Vidya et al (38) demonstrated that the measurements and volume of maxillary sinus of males were larger than females using 3D computerized tomography. Tambawala et al (39) also agreed with these results in their study using cone beam computed tomography. Most of these studies attributed the larger size of the maxillary sinus in males to sex-specific differences in body composition, weight, genetics and race.…”
Section: Discussionsupporting
confidence: 70%
“…Table-2) These findings were more or less in agreement with previous studies. 5,6,7 This study will have great importance for gender determination because when any part of the crania or fragmented Skeleton is brought before anatomist or medico -legal expert it was very difficult to predict the gender because MS being delicate, fragile difficult remain intact. Hence only denser bones can remain intact by resisting fracture and incineration.…”
Section: Methodsmentioning
confidence: 99%